Investigating the impact of P2P trading on power losses in grid-connected networks with prosumers. (1st April 2020) - Azim, M. Imran; Tushar, Wayes; Saha, Tapan K.
Highlights: A succinct overview of P2P trading in virtual and physical layers of P2P is provided. A mechanism is proposed to estimate the losses associated with P2P transactions. A large-scale P2P trading is simulated on IEEE 8500-node distribution test feeder. The overall network losses is compared with that of an existing non-P2P technique. Abstract: The extensive financial benefit that a prosumer can reap from participating in P2P trading has been shown to be unprecedented by many recent studies. However, since the actual transfer of electricity occurs over the physical network, a key question that yet to answer is: what is the repercussion of P2P trading on the power losses in grid-connected electricity networks? To this end, this paper presents a detailed physical layer analysis of P2P trading to investigate its impact on the network losses. In this paper, P2P transaction losses is defined as one part of network losses and a strategy is proposed to trace P2P transaction losses using effective nodes' area concept. The other portion of network losses is labelled as grid contributed losses incurred due to the power supplied by the grid to satisfy other customers within and outside effective nodes' area. Finally, this paper utilises IEEE 8500-node distribution test feeder to capture the large-scale performance of P2P trading in comparison with the existing case, in which there is no P2P trading. Several case studies are considered and the first category of simulation results demonstrate that the P2P transactions do not change the network losses, compared to the non-P2P scenario, if prosumers do not have power dispatch flexibility. Further, It is observed from the second category of simulation results that flexible power dispatch of P2P prosumers can change the network losses at some time instants of a typical day. However, the variation in 24 h network losses between P2P and non-P2P cases is found to be insignificant for a large-sized distribution network with notable residential customers for a typical sunny day.